Dampak Transformasi Pendidikan Nasional dari Kurikulum 2013 ke Kurikulum Merdeka: Kajian Literatur - Aufaa, Marsaa Alyaa; Andaryani, Eka Titi (Medan Resource Center, 2023)
The current educational system in Indonesia embraces the 2013 curriculum along with the Independent Campus Learning Curriculum (MBKM), aimed at enhancing the quality of education in the country. This article explores the consequences of transitioning and evolving from the 2013 curriculum to an independent curriculum. The research employs a library study method, focusing on gathering data from various online sources. Both Indonesian and English serve as the primary languages for the collected data. Google Scholar emerges as the predominant online reference source. The findings reveal that the implementation of the 2013 Curriculum has impacted teachers by necessitating greater creativity and innovation in their teaching methods. Moreover, this curriculum demands in-depth understanding and training for educators. Crucially, both curricula share the overarching goal of elevating the quality of education in Indonesia.